2016
DOI: 10.1302/0301-620x.98b4.36422
|View full text |Cite
|
Sign up to set email alerts
|

Amputation in patients with complex regional pain syndrome

Abstract: Amputation should be considered as a form of treatment for patients with intractable CRPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…He suggested, after gathering results, that if allodynia is present at the level of amputation it can lead to recurrence. On the other hand, results from Bodde et al 19 and Midbari et al 23 did not support this idea. Mitton et al 29 and Kashy et al 30 each reported one case with amputation of a leg followed by significant improvement in quality of life and rehabilitation.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…He suggested, after gathering results, that if allodynia is present at the level of amputation it can lead to recurrence. On the other hand, results from Bodde et al 19 and Midbari et al 23 did not support this idea. Mitton et al 29 and Kashy et al 30 each reported one case with amputation of a leg followed by significant improvement in quality of life and rehabilitation.…”
Section: Resultsmentioning
confidence: 86%
“…Care was taken while synthesizing the results to keep in view the quality of these studies in order to minimize bias and to assess true effect, size and direction of treatment. Studies by Midbari et al 23 and Bodde et al 24 were designed scientifically considering the restraints of complexity and rarity of CRPS. These successfully managed to recruit and compare control groups, and enabled analysis of demographics and consideration of confounders (see Table 3 for examples of excluded study).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplies of the study medication dispensed on day 1 and day 2 post randomisation were blinded (and the IVIg prescribed on days 43 and 64 was open label). Blinding was achieved by preparing the investigational medicinal product/active and placebo solution (0.1% albumin in normal saline) into bottles of identical appearance, including the labelling and the batch numbers/expiry dates.…”
Section: Randomisation and Blindingmentioning
confidence: 99%
“…[40][41][42] This remains an area of large unmet need, a fact that is also underpinned by the recently discussed, patient-driven, generally futile approaches to achieve pain relief by surgical removal of the painful limb. 43 The trial strengths include the multicentre set-up, the size, the swift recruitment to plan, the high patient retention (low withdrawal) and the high patient adherence. Patient demographics and disease characteristics are typical for those with long-standing CRPS, as seen in secondary and tertiary care.…”
Section: Limb Temperature and Volumementioning
confidence: 99%